Regulation of Crop Quality and Stress Responses (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on the mechanisms of crop response to abiotic stresses and quality formation, which are an important basis for breeding high-quality and stress-resistant varieties, especially addressing global climate change. In addition, crop adversity adaptability is closely related to the quality of agricultural products. Therefore, understanding the mechanisms that crops use to respond to environmental changes is of great significance to improve their quality.